Mesurer et comparer les compétences des élèves : les leçons de la réforme du PASEC - Hélène Charton (Les éditions de la Maison des sciences de l'Homme, 2017)
This article focuses on the PASEC learning outcomes' measurements tools. Since 2012, the program has started to reform its measurement tools which are now based on psychometrics. This technical shift has changed the rationality of the program which aims at measuring and comparing primary student's competencies in French and Maths at a regional level. This article explores both the material and technical aspects of the reform, and their consequences in the field of international evaluation programs. What does this kind of reform process tells about the conduct and evolution of international education public policies in Africa?